P395 Acceptability of point of care testing for Chlamydia trachomatis in adolescents: if we make it, will they take it?. (14th July 2019) - Pastolero, Peter; Suss, Amy; Hammerschlag, Margaret
Abstract : Background: Women 15–19 yo have the highest prevalence of C. trachomatis (Ct) infection in the US. Despite the increase in the number of cases reported, chlamydia may still be under reported as the majority of patients do not have symptoms. Point of care tests (POCT) for Ct and other STIs are currently under development. Should these tests be made available for purchase over the counter (OTC)? Methods: An anonymous 12-item questionnaire was administered to patients attending the Adolescent clinic at University Hospital of Brooklyn, NY. The clinic serves an inner-city population that is predominantly African American and Caribbean American. Results: Completed questionnaires were obtained from 99 adolescents, 12–21 yo, median 18, 74 females, 25 males. 86 responders identified themselves as straight; 1 girl as gay, 12 as bisexual. Only 27% of responders (17% girls, 44% boys) reported an adequate knowlege of Ct infection including transmission and complications. 16 girls and 3 boys reported prior positive test for Ct, all stated they were treated but 2 girls did not inform their sexual partners. Only 43.3% indicated that they would be interested in purchasing a Ct OTC (9(36%) boys, 34(46%) girls), 62% were willing to pay 20 or less. Although almost 100% indicated that they would report to their doctor and get treatment for partner, 4 would not inform their partners. Conclusion: Less than half of the respondants indicated they would buy an OTC for Ct if available. Many of these young people also had poor understanding of the transmission and risks of Ct infection. Cost was also an issue, with the majority willing to pay 20 or less. Especially worrisome was that a small number were unwilling to notify their partners of a positive test, and had not done so in the past. The impact on linkage to care may have important public health implications. Disclosure: No significant relationships.